2023
DOI: 10.7759/cureus.34318
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sickle Cell Hemoglobinopathy on Pregnancy, Labor, Puerperium, and Fetal Outcome: A Retrospective Cohort Study From a Single Centre

Abstract: Introduction: Sickle cell disease (SCD) is a major risk factor as far as pregnancy and obstetric complications are concerned. It possesses major perinatal and postnatal mortality. The management of pregnancy along with SCD requires a multispecialty team consisting of hematologists, obstetricians, anesthesiologists, neonatologists and intensivists.Objectives: The objective of this study was to investigate the effect of sickle cell hemoglobinopathy on pregnancy, labor, puerperium, and fetal outcome in the rural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…In the present study, this risk begins around the 24th week and increases gradually until the 36th week. Several studies have shown that acute sickle cell manifestations, particularly vaso-occlusive crises, increase in frequency and severity with gestational age [33][34][35][36][37]. This aggravation of the anemia exposes to the increased risk of transfusions during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, this risk begins around the 24th week and increases gradually until the 36th week. Several studies have shown that acute sickle cell manifestations, particularly vaso-occlusive crises, increase in frequency and severity with gestational age [33][34][35][36][37]. This aggravation of the anemia exposes to the increased risk of transfusions during pregnancy.…”
Section: Discussionmentioning
confidence: 99%